12*(x+7)=4*(x-3)

Simple and best practice solution for 12*(x+7)=4*(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12*(x+7)=4*(x-3) equation:



12(x+7)=4(x-3)
We move all terms to the left:
12(x+7)-(4(x-3))=0
We multiply parentheses
12x-(4(x-3))+84=0
We calculate terms in parentheses: -(4(x-3)), so:
4(x-3)
We multiply parentheses
4x-12
Back to the equation:
-(4x-12)
We get rid of parentheses
12x-4x+12+84=0
We add all the numbers together, and all the variables
8x+96=0
We move all terms containing x to the left, all other terms to the right
8x=-96
x=-96/8
x=-12

See similar equations:

| 12+3y=2 | | 3/4x-9x=-20 | | 45=-7t+2t | | 3(y-5)=3(y+5) | | -7.7n=8-9.7n | | 3x+38=77 | | 8(6v+4)+7=+4(2v) | | -72=2z+7z | | 140149–r= | | 7x*5/24x=-2.4 | | 20+8b=2+5(4b-6) | | 4x6x+3=x | | H5x-8=22 | | w/7-4=2.5 | | 8x-40+3x=360 | | 0.5+8.4x=-1 | | 4x-7+2x=-7(1+3x) | | 5x=11° | | 5x2x=-1 | | x*2+x-210=0 | | 5(y-8)+5=5y-35 | | 6=x/5+12 | | -7x-84=26-12x | | 2x^2+11x-434=0 | | z/6-2=1 | | x^2+x=3/4 | | 32.50t+5=28.75+20 | | 3x+15°=2x+4° | | 10(x+2)=140 | | 3.7x-4.6=1.2x+5.4 | | 0*x=9 | | x+7=18- |

Equations solver categories